Determining The Effectiveness Of Tasik Harapan And Tasik Aman As Flood Ponds At Universiti Sains Malaysia - Fitri, Arniza (2012)
Flooding is a common natural disaster in Malaysia triggered by heavy rainfall. Urbanization that increases the construction of paved areas, subsequently raise surface runoff and reduce time of concentration. It increases flood magnitude and so that leads to greater flood problems as what has happened at Universiti Sains Malaysia (USM) Main Campus area. USM Main Campus Malaysia has experienced flood problems since its development in 1971. Tasik Harapan and Tasik Aman were constructed in 1990 as recreation ponds and have also functioned as flood ponds. Unfortunately, the flood problem still occurs persistently.